Heparin-mediated dimerization of follistatin. Issue 4 (February 2021) - Walker, Ryan G; Kattamuri, Chandramohan; Goebel, Erich J; Zhang, Fuming; Hammel, Michal; Tainer, John A; Linhardt, Robert J; Thompson, Thomas B
Heparin and heparan sulfate (HS) are highly sulfated polysaccharides covalently bound to cell surface proteins, which directly interact with many extracellular proteins, including the transforming growth factor-β (TGFβ) family ligand antagonist, follistatin 288 (FS288). Follistatin neutralizes the TGFβ ligands, myostatin and activin A, by forming a nearly irreversible non-signaling complex by surrounding the ligand and preventing interaction with TGFβ receptors. The FS288-ligand complex has higher affinity than unbound FS288 for heparin/HS, which accelerates ligand internalization and lysosomal degradation; however, limited information is available for how FS288 interactions with heparin affect ligand binding. Using surface plasmon resonance (SPR) we show that preincubation of FS288 with heparin/HS significantly decreased the association kinetics for both myostatin and activin A with seemingly no effect on the dissociation rate. This observation is dependent on the heparin/HS chain length where small chain lengths less than degree of polymerization 10 (dp10) did not alter association rates but chain lengths >dp10 decreased association rates. In an attempt to understand the mechanism for this observation, we uncovered that heparin induced dimerization of follistatin. Consistent with our SPR results, we found that dimerization only occurs with heparin molecules >dp10. Small-angle X-ray scattering of the FS288 heparin complex supports that FS288 adopts a dimeric configuration that is similar to the FS288 dimer in the ligand-bound state. These results indicate that heparin mediates dimerization of FS288 in a chain-length-dependent manner that reduces the ligand association rate, but not the dissociation rate or antagonistic activity of FS288.